RgIA4 Potently Blocks Mouse α9α10 nAChRs and Provides Long Lasting Protection against Oxaliplatin-Induced Cold Allodynia - Christensen, Sean B.; Hone, Arik J.; Roux, Isabelle; Kniazeff, Julie; Pin, Jean-Philippe; Upert, Grégory; Servent, Denis; Glowatzki, Elisabeth; McIntosh, J. Michael (Frontiers in Cellular Neuroscience, 2017)
Transcripts for α9 and α10 nicotinic acetylcholine receptor (nAChR) subunits are found in diverse tissues. The function of α9α10 nAChRs is best known in mechanosensory cochlear hair cells, but elsewhere their roles are less well-understood. α9α10 nAChRs have been implicated as analgesic targets and α-conotoxins that block α9α10 nAChRs produce analgesia. However, some of these peptides show large potency differences between species. Additionally several studies have indicated that these conotoxins may also activate GABAB receptors (GABABRs). To further address these issues, we cloned the cDNAs of mouse α9 and α10 nAChR subunits. When heterologously expressed in Xenopus oocytes, the resulting α9α10 nAChRs had the expected pharmacology of being activated by acetylcholine and choline but not by nicotine. A conotoxin analog, RgIA4, potently, and selectively blocked mouse α9α10 nAChRs with low nanomolar affinity indicating that RgIA4 may be effectively used to study murine α9α10 nAChR function. Previous reports indicated that RgIA4 attenuates chemotherapy-induced cold allodynia. Here we demonstrate that RgIA4 analgesic effects following oxaliplatin treatment are sustained for 21 days after last RgIA4 administration indicating that RgIA4 may provide enduring protection against nerve damage. RgIA4 lacks activity at GABAB receptors; a bioluminescence resonance energy transfer assay was used to demonstrate that two other analgesic α-conotoxins, Vc1.1 and AuIB, also do not activate GABABRs expressed in HEK cells. Together these findings further support the targeting of α9α10 nAChRs in the treatment of pain.